DEVELOPMENT OF MATHEMATICS LEARNING MODULES BASED ON CREATIVE PROBLEM-SOLVING ON TRIGONOMETRY MATERIAL: PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA BERBASIS CREATIVE PROBLEM-SOLVING PADA MATERI TRIGONOMETRI - Nur, Fitriani; Masita (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
The development of effective and innovative mathematics learning modules is an important effort to improve the quality of the learning process, especially in materials that require concept understanding and creative thinking skills, such as trigonometry. One model that can be used to achieve this goal is creative problem solving (CPS), which invites students to find innovative and effective solutions to complex mathematical problems. This study aims to develop a math learning module based on creative problem-solving on trigonometry material that is valid, practical, and effective. The module development was conducted using the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The test subjects involved students of SMAN 21 Gowa. The research instruments were module validation sheets, educator and learner response questionnaires, observation sheets, and learner learning outcomes tests. The research data analysis focused on analyzing the validity, practicality, and effectiveness of the creative problem-solving-based mathematics learning module on trigonometry material. The results showed that the creative problem-solving-based math learning module on trigonometry material had met the criteria of validity, practicality, and effectiveness. Thus, this learning module is suitable for use in the implementation of mathematics learning, especially in trigonometry material.